Manufacture and Strength Analysis of Ergonomic Bicycle Helmet Made from Polymeric Foam Composite Strengthened by Oil Palm Empty Fruit Bunch Fiber with Free Fall Drop Test Method - Mahadi Mahadi (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
This article contains a study report on the manufacturing of bicycle helmet models that use polymeric foam composite materials strengthened by oil palm empty fruit bunch (OPEFB). The test results of mechanical polymeric foam obtain tensile stress (σt) 1.17 MPa, compressive stress (σc) 0.51 MPa, bending stress (σb) 3.94 MPa, modulus of elasticity (E) 37.97 MPa, density ( ρ) 193 (kg / m3). The testing results of thermal conductivity (k) with ASTM C177-04 standard obtain 0.096 W/mK. Aerodynamic simulation is carried out on 5 bicycle helmet models with different variations of air ventilation formations and obtained the M4A model that best met the ergonomic criteria. The simulation results of the M4A helmet model are max 65.668 Pa of air pressure (Pu), 26,8 0C of inner wall temperature (Ti), 11.0724 m/s of air velocity (vi) and 0.89 of drag coefficient (CD). Bicycle helmet manufacturing is carried out by hand lay up method for shell layer and casting mold for liner by using GFRP polymer composite molds. Both layers are made by sandwich method with the composition of the shell layer is 100 grams resin, 15 grams glass fiber and 5 grams catalyst. The composition of the liner layer is 275 grams (50%) of unsaturated Polyester 157 BQTN-EX resin, 27.5 grams (5%) of OPEFB fiber, 247 grams (45%) of Blowing Agent Polyurethane and 27.5 grams (5%) of Methyl Ketone Perokside catalyst (MEKPO). The toughness of the helmet is tested by using a free fall drop test with the standard of Consumer Product Safety Commission (CPSC) with the height of impact 1.5 meters. The free fall drop test results are max 2.02 MPa of the impact stress of the M4A bicycle helmet model (σi) and max 283.77 joules of energy impact (Ei) which is close to the Consumer Product Safety Commission’s (CPSC) standard value of 110 joules.